2021
DOI: 10.1111/imb.12729
|View full text |Cite
|
Sign up to set email alerts
|

lnc94638 is a testis‐specific long non‐coding RNA involved in spermatozoa formation in Zeugodacus cucurbitae (Coquillett)

Abstract: Long non‐coding RNAs (lncRNAs) generally display tissue‐specific distributions, and testis‐specific lncRNAs form the highest proportion of lncRNAs in many species. Here, we presented a detailed analysis of testis‐specific lncRNAs in the melon fly, Zeugodacus cucurbitae, a highly destructive insect pest of cucurbitaceous and other related crops. Most testis‐specific lncRNAs were found to be long intergenic non‐coding RNAs (lincRNA). The size distribution of these lncRNAs ranged between 600 and 1000 nucleotides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…FISH analyses further confirmed that the ZcTSSK1 and ZcTSSK3 signal was largely confined to the transformation region where spermatids finalize their differentiation into tailed spermatozoa. The testis‐specific gene lnc94638 is similarly expressed primarily within this transformation region, and knocking down lnc94638 has been shown to impact male melon fly fertility 44 . As such, both the localization and expression patterns of ZcTSSK1 and ZcTSSK3 strongly suggest that they may function similarly as important mediators of spermatogenesis in Z. cucurbitae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FISH analyses further confirmed that the ZcTSSK1 and ZcTSSK3 signal was largely confined to the transformation region where spermatids finalize their differentiation into tailed spermatozoa. The testis‐specific gene lnc94638 is similarly expressed primarily within this transformation region, and knocking down lnc94638 has been shown to impact male melon fly fertility 44 . As such, both the localization and expression patterns of ZcTSSK1 and ZcTSSK3 strongly suggest that they may function similarly as important mediators of spermatogenesis in Z. cucurbitae .…”
Section: Discussionmentioning
confidence: 99%
“…The testisspecific gene lnc94638 is similarly expressed primarily within this transformation region, and knocking down lnc94638 has been shown to impact male melon fly fertility. 44 As such, both the localization and expression patterns of ZcTSSK1 and ZcTSSK3 strongly suggest that they may function similarly as important mediators of spermatogenesis in Z. cucurbitae. Consistent findings have also been reported in mammals.…”
Section: K a T V A V L L E P E P H A Rwn L R E I L N C S W L K A T V ...mentioning
confidence: 97%
“…Although lncRNAs have been considered as a “redundant factor” in the individual regulatory system in previous studies, more evidence has shown that lncRNAs can direct or indirectly participate in cell function regulation and the occurrence of various human diseases [ 29 ]. Accumulating studies have characterized many testis-related lncRNAs [ 30 , 31 , 32 ], but only some pieces of literature have proved that they have substantial impacts on male fertility in vivo [ 8 , 10 , 33 ]. In fact, most of the lncRNAs’ function is still enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of the machine vision technology with the male sterility technology, to single out male pupae can substantially reduce the workload involved. Li et al used the RNAi technology to interfere with the lnC94638 gene expression in Z. cucurbitae (Coquillett) males to reduce their sperm number and fertility [26]. Moreover, they used the same technology to interfere with the ZcVMP26Ab gene in females to achieve low egg hatchability [27].…”
Section: Plos Onementioning
confidence: 99%